2020
DOI: 10.1111/sji.13008
|View full text |Cite
|
Sign up to set email alerts
|

The level of naturally occurring anti‐αGal antibody predicts antibody response to polysaccharide vaccination in HIV‐infected adults

Abstract: In clinical practice, the capacity for producing anti‐carbohydrate antibodies is regarded as an entity, but supportive evidence is lacking. We hypothesized that the outcome of the gold standard test for clinical assessment of this capacity, antibody response to polysaccharide vaccination, correlated with the level of the abundant naturally occurring anti‐carbohydrate antibody, anti‐αGal. To perform an exploratory study, 47 HIV‐infected adults were recruited from a vaccine trial. Participants received a 23‐vale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Entirely different approaches for assessing the antibody competence of patients may also be of clinical interest. We recently reported that the level of naturally occurring antibodies against terminal galactose- α -1,3-galactose (anti-αGal) predicts the outcome of diagnostic vaccination in HIV infected adults ( 34 ). Anti-αGal antibodies are of particular interest in patients with suspected antibody deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Entirely different approaches for assessing the antibody competence of patients may also be of clinical interest. We recently reported that the level of naturally occurring antibodies against terminal galactose- α -1,3-galactose (anti-αGal) predicts the outcome of diagnostic vaccination in HIV infected adults ( 34 ). Anti-αGal antibodies are of particular interest in patients with suspected antibody deficiency.…”
Section: Discussionmentioning
confidence: 99%